CHIZIQLI EMAS ALGEBRAIK TENGLAMALARNI YECHISH USULLARI - Kalmuratova, S.M.; Tursınbekova, I.J.; Muxiyatdinov, J.K. (SCIENCE and SOCIETY, 2024)
This article describes the Lin Shinge and Friedman methods of prime factorization of polynomials, which are widely used in the computational practice of solving algebraic equations, and their application to the solution of given exact equations.